Measuring the impact of Lean tools on the cost–time investment of a product using cost–time profiles (2007)
Traditional costing systems consider the accumulation of costs, but not their timing. Value stream mapping presents a good picture of the time consumed and operations performed for the production of a product within a manufacturing facility, but it does not track the accumulation of costs. The cost–time profile (CTP) is a tool that follows the accumulation of cost in the manufacturing of a product through time; and it finds the cost–time investment (CTI), which is an indicator of the use of resources in the manufacturing of a product through quantities and timing. In this paper, the expected impact of Lean implementations on the CTP and CTI is discussed. The CTP is proposed as a useful tool for the evaluation of the improvements achieved by the implementation of Lean tools and techniques.